Pengenalan Tehnik Ekstraksi Minyak non edible Berbasis Baku Lokal di SMKPP Negeri Mataram - Murniati Murniati; Dedy Suhendra; Erin Ryantin Gunawan; Sri Seno handayani; Baiq Yusmi Aolinnir Rahmah; Fahrurazi Fahrurazi; Suryono Suryono (Jurnal Gema Ngabdi, 2023)
Non-edible oils are not used as food, which comes from plants that are not used properly, but are very abundant and even become waste. These plants are able to produce high enough oil, which is around 30-80% with a composition that is almost similar to edible. The oil can be obtained by extraction. However, most people do not know how to extract these oils. Therefore, it is necessary to introduce and train on how to extract these non-edible oils, especially people who have the potential to be young entrepreneurs, one of which is SMK. SMKPP Negeri Mataram is one of the secondary schools that carries out the mission of education in the field of agriculture extensively and prepares capable and skilled human resources in agriculture. This service aims to increase the knowledge and understanding of SMKPP Negeri Mataram students about local plants that have the potential as non-edible and oil extraction training which can later become the provision of students after graduation by taking advantage of the potential and opportunities that exist around them. This service activity will be carried out in two stages, namely introduction/socialization activities about plants that have the potential as non-edible and simple oil extraction training. The results of service activities have provided additional knowledge and understanding of SMKPP Negeri Mataram students about local plants that have the potential to produce non-edible oil and simple oil extraction techniques.